2020
DOI: 10.1001/jamanetworkopen.2020.19429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Financial Incentives on Statin Adherence and Lipid Control

Abstract: IMPORTANCE Financial incentives can improve medication adherence and cardiovascular disease risk, but the optimal design to promote sustained adherence after incentives are discontinued is unknown. OBJECTIVE To determine whether 6-month interventions involving different financial incentives to encourage statin adherence reduce low-density lipoprotein cholesterol (LDL-C) levels from baseline to 12 months. DESIGN, SETTING, AND PARTICIPANTS This 4-group, randomized clinical trial was conducted from August 2013 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
1
23
1
1
Order By: Relevance
“…Our study failed to show an association of adherence-enhancing intervention and LDL-C between the intervention and control groups. In line with our ndings, a recent adherenceenhancing intervention involving nancial incentives showed increased adherence but similar LDL-C values among the experimental groups [30]. These results underline the importance of directly measuring clinical outcomes, rather than mere adherence, in trials with behavioral interventions.…”
Section: Discussionsupporting
confidence: 89%
“…Our study failed to show an association of adherence-enhancing intervention and LDL-C between the intervention and control groups. In line with our ndings, a recent adherenceenhancing intervention involving nancial incentives showed increased adherence but similar LDL-C values among the experimental groups [30]. These results underline the importance of directly measuring clinical outcomes, rather than mere adherence, in trials with behavioral interventions.…”
Section: Discussionsupporting
confidence: 89%
“…As described elsewhere, participants were eligible for the trial if they had a daily statin prescription, self-reported incomplete adherence to the statin therapy, and 1 or more of the following: diabetes, ASCVD with elevated LDLC levels, 10-year ASCVD risk score of greater than 7.5%, or high LDLC levels (>190 mg/dL [to convert to millimoles per liter, multiply by 0.0258]). 12 , 13 , 22 All participants received electronic pill containers, which transmitted a signal to the study team at each opening as a measure of adherence. Participants also received daily reminders to take their statin.…”
Section: Methodsmentioning
confidence: 99%
“…The Habit Formation trial, a randomized clinical trial described elsewhere, 12 , 13 tested the ability of 6 months of financial rewards for daily statin therapy adherence to establish longer-term adherence habits. The primary outcome was change in low-density lipoprotein cholesterol (LDLC) levels at 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…The primary intention-to-treat analysis modeled change in LDL-C level to months as a linear function of the intervention group and LDL-C level at baseline with adjustment by study site (Penn Medicine or Lancaster General Hospital) and used multiple imputation to account for missing data (16% of LDL-C levels at 12 months, balanced across groups). 20 , 39 In the primary analysis, stage 1 tested whether the mean change in LDL-C level at 12 months differed between each intervention group and the control group using a Holm-Bonferroni correction for 3 contrasts. If differences were found, stage 2 would contrast each pair of interventions that differed from the control in stage 1.…”
Section: Methodsmentioning
confidence: 99%
“… 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 In studies of other health behaviors, such as medication adherence and weight loss, however, financial incentives have not consistently improved outcomes. 17 , 18 , 19 , 20 , 21 , 22 The effectiveness of financial incentives may depend on the design, timing of feedback, and the nature of the behavior being incented, as well as the ability to measure the targeted health behavior accurately and nonintrusively. 23 , 24 Statins are taken daily, which requires organization, and do not perceptibly improve short-term quality of life, so daily financial incentives for taking the statin (a process-of-care incentive) could help nonadherent users overcome present bias (the cognitive tendency to value behaviors with immediate rewards while undervaluing longer-term consequences).…”
Section: Introductionmentioning
confidence: 99%